A case of bilateral inguinal hernia associated with Marfan syndrome - Yoshiki Yamaguchi; Masahiro Fukuhara; Tomoko Izaki (Elsevier, 2022)
Marfan syndrome, a connective tissue disease, is associated with a high incidence and recurrence rate of inguinal hernia. We herein report a three-year-old boy with bilateral inguinal hernia associated with Marfan syndrome. While preoperative contrast-enhanced computed tomography (CT) revealed a left indirect inguinal hernia and a right direct inguinal hernia, laparoscopy showed bilateral patent processus vaginalis (PPV) and vulnerability of the abdominal wall at the bilateral medial inguinal fossae. In addition to laparoscopic percutaneous extraperitoneal closure (LPEC), open iliopubic tract repair was also performed. To our knowledge, this is the first report of a therapeutic strategy for pediatric inguinal hernia with Marfan syndrome.